Interlaboratory comparison for electric energy in Panama and the Dominican Republic: a key exercise to maintain confidence and international recognition (INNOTEC, 2024)
This article describes the results of a comparison between two national metrology laboratories, located in Panama and the Dominican Republic, regarding electrical energy measurements carried out from August to October 2023. The intercomparison was developed with the objective of supporting calibration and measurement capabilities (CMC) of INDOCAL (Dominican Republic) in the magnitude of electrical energy, specifically for the calibration service of standards of this magnitude. To this purpose, the comparison of their measurement results was carried out against those issued by a laboratory with a recognized CMC and published in the database of the International Bureau of Weights and Measures (BIPM), in this case CENAMEP AIP (Panama). Because the participants consistently had an En < 1, it was not necessary to implement corrective actions in the participating laboratories to improve their electrical energy standard calibration processes. The results of this study strengthen the confidence of the technical management of the two participating laboratories and, consequently, of the national quality infrastructure in both countries.
Keywords: normalized error; reference standard; traceability; uncertainty